1970
DOI: 10.3329/bjvm.v6i2.2330
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> efficacy of some indigenous plants on the inhibition of development of eggs of <i>Ascaridia galli</i> (Digenia: Nematoda)

Abstract: In vitro efficacy of five indigenous plants namely Bishkatali (Polygonum hydropiper), Neem (Azadirachta indica), Papaya (Carica papaya), Korolla (Momordica charantia) and Mahogany (Swietenia macrophylla) were studied against the development of Ascaridia galli eggs from July 2007 to May 2008. Fresh juice, extracts and dust of leaves were tested. Fresh juice of leaves were trialed at 5%, 10% and 20% concentrations; aqueous, ethanol and methanol extracts were used at 1%, 2% and 4% concentrations and dusts of leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…The extract was further evaporated in a waterbath to produce a concentrated extract. The concentrated extract was then stored at the temperature of 5°C and ready to use (Islam et al, 2008;Iqbal et al, 2013;Indrasanti et al, 2015).…”
Section: Preparation Of Garlic Extractmentioning
confidence: 99%
“…The extract was further evaporated in a waterbath to produce a concentrated extract. The concentrated extract was then stored at the temperature of 5°C and ready to use (Islam et al, 2008;Iqbal et al, 2013;Indrasanti et al, 2015).…”
Section: Preparation Of Garlic Extractmentioning
confidence: 99%
“…Particularly, fresh juice (at 5, 10 and 20%), aqueous extract (at 1, 2 and 4%), ethanol extract (at 1, 2 and 4%), methanol extract (at 1, 2 and 4%), and powder (at 10 and 20%) of leaves of Azadirachta indica, Carica papaya, Momordica charantia, Polygonum hydropiper, and Swietenia macrophylla inhibited the development of A. galli eggs, with C. papaya showing the highest efficacy 92% when the concentration was 4% (Islam et al, 2008). Another experiment using larvae development assays of A. galli revealed that different types of extracts (hexane; ethylacetate; acetone; methanol; chloroform) of Aloe secundiflora at 5, 10, 20, 40 and 50 mg/ml have inhibitory effects on the parasite's development (Kaingu et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kaushik et al (1981) Alcohol extract at 25 mg/ml Alcohol extract at 10 mg/ml Alcohol extract at 200 mg/ml Alcohol extract at 100 mg/ml Paralysis; Death (Lal et al, 1976) Cleome viscosa Seeds Crude alcohol and aqueous extracts at 10, 50 and 100 mg/ml Paralysis; Death (Mali et al, 2007) Thespesia lampas Roots Aqueous extracts at 10, 20 and 50 mg/ml. Paralysis; Death (Kosalge and Fursule, 2009) Inhibition of egg development (Islam et al, 2008) Aloe secundiflora Leaves Hexane, ethylacetate, acetone, methanol, and chloroform extracts at 5, 10, 20, 40 and 50 mg/ml Inhibition of larvae development (Kaingu et al, 2013) or alcohol distillation, extraction with non-aqueous solvents, etc.) can modify the active substances and associated compounds in the final product (Tariq et al, 2009;Windisch et al, 2009).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Ekstrak daun A. indica (Khokon et al, 2004;Saha et al, 2015), ekstrak Curcuma longa (Alrubaie, 2015), ekstrak etanol kulit buah jeruk (Abdelqader et al, 2012), ekstrak daun Bishkatali (Polygonum hydropiper) (Islam et al, 2008) mempercepat waktu paralisis dan mortalitas A. galli secara in vitro. Lalchhandama et al (2009) dan Roy et al (2012) …”
Section: Traditional Medicine Journal 22(3) 2017unclassified